2022
DOI: 10.1029/2021je007130
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Troughs on Asteroid 4 Vesta Accommodate Opening‐Mode Displacement

Abstract: Asteroid 4 Vesta hosts two sets of enormous troughs, Divalia Fossae that encircle two‐thirds of the equator and Saturnalia Fossae located in the northern hemisphere. These troughs were interpreted as grabens, thus invoking faulting. The trough sizes, their linear arrangement, and overall morphology leave no doubt that their origin is tectonic, but structures other than faults have not been considered. To test if they are fault‐related or formed by accommodating opening‐mode displacement (i.e., jointing) withou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…There are areas in Divalia Fossae that might suggest a stronger concentration of howarditic regolith (rather than more teal tones, which would indicate a more diogenite-rich regolith likely associated with Rheasilvia ejecta). If so, this could indicate a later opening of these fossae after ejecta emplacement (Cheng et al 2021;Cheng & Klimczak 2022a, 2022b. However, these observations would also be consistent with a scenario in which thin Rheasilvia ejecta was thoroughly mixed with underlying howardite-rich regolith through tectonic activity and subsequent settling and mass wasting along ridge slopes.…”
Section: Fossaesupporting
confidence: 71%
“…There are areas in Divalia Fossae that might suggest a stronger concentration of howarditic regolith (rather than more teal tones, which would indicate a more diogenite-rich regolith likely associated with Rheasilvia ejecta). If so, this could indicate a later opening of these fossae after ejecta emplacement (Cheng et al 2021;Cheng & Klimczak 2022a, 2022b. However, these observations would also be consistent with a scenario in which thin Rheasilvia ejecta was thoroughly mixed with underlying howardite-rich regolith through tectonic activity and subsequent settling and mass wasting along ridge slopes.…”
Section: Fossaesupporting
confidence: 71%
“…6a ). The troughs were believed to be tectonic features formed later than the Rheasilvia basin, as either fault-controlled graben 40 or opening-mode cracks 41 . However, many of the troughs appear as closely aligned pit chains that have raised rims (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the pit chains are named: Robigalia Catena (Figure 7a) and Albalonga Catena (AC) (Figure 7b). One of the Divalia Fossae troughs shows a direct transition into the AC pit crater chain; the trough narrows toward its tips and directly transitions into a pit crater chain, which aligns with smaller pits at the end of the trough (Buczkowski et al., 2014; Cheng & Klimczak, 2022). These pit chains resemble the nature of secondary craters from Orientale (Figure 7f), which exhibit a set of parallel chains of bowl‐shaped craters linearly connected to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Schäfer et al (2014) and Yingst et al (2014) reported that they are primarily composed of parallel running troughs and ridges (Figures 7c and 7d). Cheng and Klimczak (2022) reported that most of the troughs have bowl-shaped cross-sectional geometries, a distinct flat floor is not the most common trough geomorphology, they are heavily degraded, and there is no diagnostic evidence for fault traces of graben or joint walls, although they concluded that the troughs are of tectonic origin. On the other hand, Buczkowski et al (2012) showed several examples of fault linkages and fault slip movement in Divalia and Saturnalia Fossa.…”
Section: The Volume Of Ejecta Launched Faster Thanmentioning
confidence: 99%